Combatting Covid-19 - On Relative Performance of the Indian States - Sugata Marjit; Anish Kumar Mukhopadhyay; Medha Chatterjee (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The purpose of this paper is to construct a relative performance index for the States in India in terms of their performance in combatting Covid-19 pandemic. The data is analyzed up to August, 2020, though the methodology used can be readily extended to update the index. The methodology can be applied to other developing countries with similar background. We use population density and the extent of tests conducted to fine tune the index. The association between per capita health expenditure and relative performance indices reveals that there are states where relatively sound health infrastructure has not ensured better performance in curing patients and those relatively weak have done better. But with a multi-dimensional health infrastructure index such anomaly tends to disappear.
Keywords: I12; I15; 330; infectious disease; morbidity; mortality; human development; population health